Pressure–volume loop validation of TAPSE/PASP for right ventricular arterial coupling in heart failure with pulmonary hypertension. (9th November 2020) - Schmeisser, Alexander; Rauwolf, Thomas; Groscheck, Thomas; Kropf, Siegfried; Luani, Blerim; Tanev, Ivan; Hansen, Michael; Meißler, Saskia; Steendijk, Paul; Braun-Dullaeus, Ruediger C
Abstract: Aims: The aim of this study was to validate the tricuspid annular plane systolic excursion/systolic pulmonary artery (PA) pressure (TAPSE/PASP) ratio with the invasive pressure–volume (PV) loop-derived end-systolic right ventricular (RV) elastance/PA elastance (Ees/Ea) ratio in patients with heart failure with reduced ejection fraction (HFREF) and secondary pulmonary hypertension (PH). Methods and results: The relationship of TAPSE and TAPSE/PASP with RV-PV loop (single-beat)-derived contractility Ees, afterload Ea, and Ees/Ea was assessed in 110 patients with HFREF with and without secondary PH. The results were compared with other surrogate parameters such as the fractional area change/PASP ratio. The association of the surrogates with all-cause mortality was evaluated. In patients with PH ( n = 74, 67%), TAPSE significantly correlated with Ees ( r = 0.356), inverse with Ea ( r = −0.514) but was most closely associated with Ees/Ea ( r = 0.77). Placing TAPSE in a ratio with PASP slightly reduced the relationship to Ees/Ea ( r = 0.71) but was more closely related to the parameters of PA vascular load, diastolic RV function, and RV energetics. The area under the curve of TAPSE/PASP and TAPSE for discriminating overall survival in receiver operating characteristic analysis was not different ( P = 0.78. Prognostic relevant cut-offs were 17 mm for TAPSE and 0.38 mm/mmHg for TAPSE/PASP. Both parameters in multivariate cox regression remained independently prognostically relevant. Conclusion: TAPSE is an easily and reliably obtainable and valid surrogate parameter for RV–PA coupling in PH due to HFREF. Putting TAPSE into a ratio with PASP did not further improve the coupling information or prognostic assessment. Trial Identifier: DRKS—German Clinical Trials Register (DRKS00011133; https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00011133 ).